2018
DOI: 10.7196/ajhpe.2018.v10i2.971
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported generic learning skills proficiency: Another measure of medical school preparedness

Abstract: ResearchThe contribution of discipline-independent cognitive skills to achieving success in higher education is increasingly acknowledged. [1][2][3][4][5][6] These skills are considered to be 'important for individuals both as learners in foundation education and training, and as future employees in changing and flexible work roles' . [6] Referred to as key skills, [7] generic graduate attributes [8] or generic skills that underpin lifelong learning, [9] they usually relate to six broad categories of skills: n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In Table 2, categories and subcategories of the measured generic skills are presented in greater detail. Most of the these studies that measured sets of generic skills utilized surveys (e.g., Jackson, 2014aJackson, , 2015Pita et al, 2015;Prokofieva et al, 2015;Abayadeera and Watty, 2016;Joseph et al, 2016;Monteiro et al, 2016;He et al, 2017;Burch et al, 2018;Akhmetshin et al, 2019;López et al, 2019). Control and experimental groups were also used in study designs (Guo, 2019;Tomasson Goodwill et al, 2019).…”
Section: Sets Of Generic Skillsmentioning
confidence: 99%
“…In Table 2, categories and subcategories of the measured generic skills are presented in greater detail. Most of the these studies that measured sets of generic skills utilized surveys (e.g., Jackson, 2014aJackson, , 2015Pita et al, 2015;Prokofieva et al, 2015;Abayadeera and Watty, 2016;Joseph et al, 2016;Monteiro et al, 2016;He et al, 2017;Burch et al, 2018;Akhmetshin et al, 2019;López et al, 2019). Control and experimental groups were also used in study designs (Guo, 2019;Tomasson Goodwill et al, 2019).…”
Section: Sets Of Generic Skillsmentioning
confidence: 99%
“…University students perceive that collaboration skills develop the least during their studies, even though they are important working life skills (García-Aracil and Van der Velden, 2008;Tuononen et al, 2019a), whereas analyzing skills are well learned at university (Murdoch-Eaton et al, 2016;Tuononen et al, 2019a). Generic skills are also needed in learning, and medical students need them for their academic success (Murdoch-Eaton and Whittle, 2012;Winston et al, 2012;Burch et al, 2018). Therefore, it is important to examine how students perceive the learning of generic skills in health professions education.…”
Section: Introduction Learning Generic Skillsmentioning
confidence: 99%
“…The mnemonic was generally well perceived by teachers and students alike. The article by Burch et al [9] reminded me of Paulo Freire's [10] work, Pedagogy of the Oppressed. Freire believed that learners do not enter tertiary institutions as blank slates.…”
Section: Editorialmentioning
confidence: 99%
“…Freire believed that learners do not enter tertiary institutions as blank slates. Burch et al [9] studied the self-reported proficiency levels of medical students in six categories of generic learning skills and found a significant relationship with pre-university admission aptitude test scores, information technology proficiency on entry to university and early academic performance at university. Furthermore, academically weak students did not overestimate their skills proficiency.…”
Section: Editorialmentioning
confidence: 99%